EFFECT OF SURFACE TREATMENT WITH REMINERALIZING ON THE COLOR STABILITY AND ROUGHNESS OF ESTHETIC RESTORATIVE MATERIALS - R., Prabhakar A.; T., Mahantesh; D., Vishwas T.; Kabade, Aparna (Archives of Oral Research, 2009)
OBJECTIVES: The purpose of the study was to evaluate and compare the in vitro effect of fluoride varnish, APF gel and MI paste on the color stability and surface roughness of esthetic restorative materials. MATERIAL AND METHODS: 60 disks of each conventional glass ionomer and resin composite were made using molds of 1.2 cm x 2 mm. All the specimens were suspended in artificial saliva for 48 hours at 37ºC. Subsequently, fluoride varnish, APF gel, and MI paste were applied to all the subgroups except the controls. All the specimens were again suspended in artificial saliva and incubated at 37ºC for 24 hours. After incubation, they were cleaned using a toothbrush and toothpaste, and stored in the artificial saliva for 1 week. During this period, the specimens were subjected to color and surface roughness measurement. RESULTS: Measurements were expressed as mean ± standard deviation and compared between two groups by Student’s t test. One way ANOVA was used for multiple group comparison and Tukey’s test for pair wise comparison. CONCLUSION: The deterioration of GIC material was more rapid compared to composites when fluoride varnish, APF gels and GC Tooth Mousse were applied. The use of remineralizing agents on esthetic restorative materials causes changes in color and surface texture.